Analisis Keterampilan Membaca Siswa pada Pembelajaran Bahasa Indonesia di Kelas V SD Negeri 17 Bilah Barat - Romadhani, Putri Syahri; Solihah Titin Sumanti (Islamic Education, 2023)
This study aims to describe the Indonesian language learning process in the fifth grade of SD Negeri 17 Bilah Barat, to describe students' reading skills in Indonesian language learning in the fifth grade of SD Negeri 17 Bilah Barat, and to identify the factors hindering students' reading skills. Based on these objectives, the problems can be formulated as follows: how the learning process and students' reading skills are, as well as the supporting and hindering factors of students' reading skills in Indonesian language learning in the fifth grade of SD Negeri 17 Bilah Barat. Based on the objectives and problem formulation explained, this study uses a descriptive qualitative research method. Data collection methods in this study include observation, interviews, and documentation. The results of this study indicate that 8 out of 23 students do not experience difficulties in reading skills, while 15 out of 23 students in the fifth grade-B of SD Negeri 17 Bilah Barat experience difficulties in reading skills.